Morphological study of the perireticular nucleus in human fetal brains - (:unkn) unknown (WILEY, 2004)
The perireticular nucleus consists of scattered neurons that are located in the internal capsule. The presence of perireticular neurons in the rat, ferret, cat and human has been described previously. Evidence suggests that the perireticular neurons in various species decrease in number with increasing gestation, but in humans this finding has not been supported by quantitative data. This study aimed to investigate (1) the morphology of the human fetal perireticular neurons, (2) the average number of perireticular neurons within the anterior and posterior crus of the internal capsule per unit area, and (3) the magnitude and the stage of neuronal loss in the human perireticular nucleus subsequent to maturation. Nissl-stained sections of the internal capsule of human fetal brains of 24, 26.5, 32, 35, 37 and 39 weeks of gestation showed a number of clearly distinguishable large perireticular and small microglia cells. A regular increase of both perireticular and microglial cells was observed up to 32 weeks of gestation, after which a dramatic reduction in the number of both perireticular and microglia cells was observed. The average number of perireticular and the microglia cells per unit area, located within the posterior crus, was more than in the anterior crus of the internal capsule. In the adult, no perireticular neurons were detected within the internal capsule. The results show that perireticular neurons are not restricted to the region lateral to the thalamus and medial to the globus pallidus (posterior crus) but are also present at the region lateral to the caudate nucleus and medial to the globus pallidus (anterior crus).
Keywords: human fetal brain; internal capsule; perireticular; THALAMIC RETICULAR NUCLEUS; DEVELOPING RATS; FERRETS; EXPRESSION; NEOCORTEX; PATTERNS; PROJECT; NEURONS; ADULT; CATS